2022
DOI: 10.3390/polym14051008
|View full text |Cite
|
Sign up to set email alerts
|

A Sprayable and Visible Light Rapid-Cured Strippable Film for Surface Radioactive Decontamination

Abstract: Strippable film is effective for removing radioactive contamination. However, it still has some limitations, such as the long curing time (about 30 min~24 h) and the requirement of organic solvents. To address these issues, we report a simple protocol to prepare strippable decontamination films using liquid polybutadiene (LPB) and tert-butyl acrylate (TBA) as the raw materials without solvent and using camphorquinone/ethyl 4-dimethylaminobenzoate (CQ/EDB) as a photoinitiator, where the film was formed under ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
0
0
Order By: Relevance
“…Peelable/strippable coatings are defined as temporary coatings that may be peeled off as continuous and sizeable films from the substrate after the service term [13]. Examples of commercially available peelable coatings used for decontamination are ALARA 1146, DeconGel 1108, TLC Free, Isotron Radblock, and InstaCote CC Wet/CC Strip [14]. It has been observed that the curing times vary, depending on the coating thickness, between 4 and 10 h for Stripcoat TLC Free™, 18 and 32 h for DeconGel ® 1108 or 4 and 24 h for CC Wet/CC Strip [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Peelable/strippable coatings are defined as temporary coatings that may be peeled off as continuous and sizeable films from the substrate after the service term [13]. Examples of commercially available peelable coatings used for decontamination are ALARA 1146, DeconGel 1108, TLC Free, Isotron Radblock, and InstaCote CC Wet/CC Strip [14]. It has been observed that the curing times vary, depending on the coating thickness, between 4 and 10 h for Stripcoat TLC Free™, 18 and 32 h for DeconGel ® 1108 or 4 and 24 h for CC Wet/CC Strip [15].…”
Section: Introductionmentioning
confidence: 99%
“…UV-curable strippable films have recently gained popularity due to major advantages such as faster film formation time. However, UV light is required to cure these films, which can cause skin burns and can harm the cornea and retina [14]. Ionic crosslinking may represent a better option, since a complete curing can be achieved in a few minutes, depending on the thickness of the coating, and it involves lower health risks for the operators.…”
Section: Introductionmentioning
confidence: 99%